2014
DOI: 10.1016/j.stem.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin and Transcription Transitions of Mammalian Adult Germline Stem Cells and Spermatogenesis

Abstract: Adult germline stem cells (AGSCs) self-renew (Thy1(+) enriched) or commit to gametogenesis (Kit(+) enriched). To better understand how chromatin regulates AGSC biology and gametogenesis, we derived stage-specific high-resolution profiles of DNA methylation, 5hmC, histone modifications/variants, and RNA-seq in AGSCs and during spermatogenesis. First, we define striking signaling and transcriptional differences between AGSC types, involving key self-renewal and proliferation pathways. Second, key pluripotency fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
330
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(358 citation statements)
references
References 46 publications
23
330
4
1
Order By: Relevance
“…It must be noted that while what we have identified is intriguing, we may simply be observing a downstream change to the epigenome that is not causative of the gross semen abnormalities, but is reflective of a more global causative change. Further, while there is strong data to suggest that methylation marks remain stable from the AGSC to the mature spermatozoa (Hammoud et al, 2014), this does not mean that the currently identified perturbations did not arise in the spermatogenesis cycle, in which case the stem cells would be largely unaffected. Clearly, much more investigation is required to understand the true nature of these marks and their potential impact on fertility.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It must be noted that while what we have identified is intriguing, we may simply be observing a downstream change to the epigenome that is not causative of the gross semen abnormalities, but is reflective of a more global causative change. Further, while there is strong data to suggest that methylation marks remain stable from the AGSC to the mature spermatozoa (Hammoud et al, 2014), this does not mean that the currently identified perturbations did not arise in the spermatogenesis cycle, in which case the stem cells would be largely unaffected. Clearly, much more investigation is required to understand the true nature of these marks and their potential impact on fertility.…”
Section: Discussionmentioning
confidence: 92%
“…Among the most promising marks to accomplish this are residual epigenetic alterations, including DNA methylation patterns, that are used in transcriptional regulation in the AGSC and are largely maintained throughout spermatogenesis to the mature spermatozoa (Hammoud et al, 2014). Because of the regulatory role of DNA methylation, such marks offer a potential snapshot of the events that occur early in spermatogenesis where programmatic problems may contribute to various types of sperm abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…To identify peaks of SG fractions we compared the differential peaks with published dataset (95). The differential regions of SG fraction are enriched in cell cycle and RNA processing genes.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the poised chromatin state is thought to be functionally associated with, and important for, pluripotency (Azuara et al, 2006;Bernstein et al, 2006;Mikkelsen et al, 2007). Several recent studies (Hammoud et al, 2009(Hammoud et al, , 2014Mochizuki et al, 2012;Erkek et al, 2013;Lesch et al, 2013;Ng et al, 2013;Sachs et al, 2013) have collectively shown that poised chromatin is maintained at developmentally critical gene promoters at multiple stages of male and female germ cell development in the mouse (Table 1). Germ cells represent a unique in vivo cell population: although they undergo extensive cellular differentiation as unipotent cells during gametogenesis, they nevertheless contribute to a totipotent embryo at fertilization ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is present in adult germline stem cells (Hammoud et al, 2014), which, like early fetal germ cells, can give rise to EG cell lines in culture (Kanatsu-Shinohara et al, 2004). Furthermore, differentiating adult male germ cells that have initiated or completed meiosis ( pachytene spermatocytes or round spermatids, respectively) also retain a poised epigenetic state at a majority of the same genes that are poised in early fetal germ cells, thus highlighting the maintenance of the bivalent state throughout the germline cycle (Lesch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%